Developing Seventh Grade Students' Understanding of Possessive Pronouns through Contextual Learning - Nova Evelin Saragih; Selviana Napitupulu (CV PUTRA PUBLISHER, 2025)
Grammar mastery plays a crucial role in developing students’ English proficiency; however, grammar instruction in junior high schools is often perceived as abstract and disengaging. Many students experience difficulties in understanding possessive pronouns due to traditional rule-based teaching methods that lack contextual relevance and meaningful application. This study aimed to improve seventh-grade students’ understanding of possessive pronouns through the implementation of the Contextual Learning Approach (CLA) at SMP Negeri 2 Pematangsiantar. This research employed a qualitative Classroom Action Research (CAR) design conducted in two cycles involving 32 students of class VII-5. The data were collected using tests, observation sheets, field notes, interviews, and documentation. The implementation of contextual learning activities emphasized real-life situations, such as identifying ownership through classroom objects and personal belongings, to help students construct grammatical understanding meaningfully. The findings revealed a significant improvement in students’ grammar mastery and classroom engagement. The students’ mean score increased from 60.06 in the pre-test to 83.25 in the final test, while the percentage of students achieving the minimum mastery criterion (70) improved from 37.5% to 90.6%. Qualitative findings indicated increased motivation, participation, confidence, and collaboration among students during the learning process. In conclusion, the Contextual Learning Approach effectively enhanced students’ understanding of possessive pronouns by linking grammatical concepts to real-life contexts. The study implies that contextual-based grammar instruction can create more meaningful, interactive, and student-centered learning environments, and it is recommended for teaching other grammatical topics in junior high school.